Cycloferon Efficacy in Viral and Bacterial Diseases of Children (Clinical Review) - M. G. Romantsov; L. G. Goryacheva; M. K. Bekhtereva; T. V. Sologub; A. L. Kovalenko (Антибиотики и Химиотерапия)
The authors' findings and literature data on the pharmacotherapeut efficacy of cycloferon, an interferon inductor (immunomodulators) are described. The drug effect in the treatment of various socially significant children' diseases, including acute respiratory tract viral infection, bronchial asthma, allergic conditions with infection protection disturbances, mycoplasmic infection, bronchopulmonary complications of acute respiratory tract viral infection with low intensity of free radical oxidation is indicated. The use of cycloferon at the background of vaccination was shown to provide inhibition of the autoimmune processes causing postvaccinal complications in frequently ill children. The results of the use of cycloferon in the treatment of gastrointestinal tract and intestinal infections of both the viral and bacterial genesis are discussed. Cycferon is recommended to be used for correction of the intestine dysbiosis (the microflora level came to normal in 95% of the children). The use of the drug in surgical pathology and in particular in appendicular peritonitis for decreasing the postoperative complications and correction of the immune disturbances due to chronic viral hepatitis C and B in children under the complex therapy is described. The cycloferon safety and efficacy were confirmed by the postmarketing randomized trials.